An Ethnographic-Participatory Study of Commercial Sex Workers Responding to the Problem of HIVIAIDS in Khon Kaen, Thailand - Kanato, Manop (My University, 1994)
This thesis presents the findings of a study carried out in brothels in Khon Kaen, Thailand. The study examined efforts of the "voiceless" sex workers to organize in order to increase their control over decision-making processes. It also analyzed the difficulties, social forces, structures and ideologies which maintain an inequitable distribution of power. The broader aim was to clarify the notion of people's participation in order to make it operationally more useful with respect to AIDS prevention intervention to sex workers. A technocratic approach to issues of AIDS prevention and control among sex workers was rejected. The study embraced a number of complementary activities including: situation analysis of AIDS in the Thai context, specifically in the northeast, ethnographic study of the sex industry, and participatory action research.
This study was initiated in late 1991 and completed in 1993. It was carried out in six brothels in downtown Khon Kaen. The study occurred in 4 phases: 1) situation assessment in which historical and documentary analysis were utilized ethnographic research on sex workers which served as a basis for constructing culturally appropriate interventions, 3) participatory action research emphasizing self determination of sex workers on AIDS prevention and control, and 4) evaluation of this "experiment." The research attempts to balance "classic ethnography" and "applied participatory research" to an AIDS prevention program for sex workers in Thailand. It was carried in collaboration with health professionals, landlords, pimps, and sex workers. Groups met and worked together in brothels to discuss the findings. Results were also presented to local health authorities.
This study illustrates the opportunities for and the formidable difficulties of participation by sex workers in Thailand. Without strong support for non-formal AIDS education and self determination by sex workers, there is little chance that they can negotiate safe sex and make decisions concerning AIDS prevention.
Keywords: thailand; HIV/AIDS; commercial sex workers; khon kaen; Anthropology; Biological and Physical Anthropology; Other Anthropology; Social and Cultural Anthropology; Anthropology